2004
DOI: 10.1021/jm030262m
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Water-Soluble Pincer Silver(I)−Carbene Complexes:  A Novel Antimicrobial Agent

Abstract: Silver(I)-2,6-bis(ethanolimidazolemethyl)pyridine hydroxide (4a) and silver(I)-2,6-bis(propanolimidazolemethyl)pyridine hydroxide (4b) are water-soluble silver(I)-carbene complexes that were synthesized in high yield by reacting silver(I) oxide with N-substituted pincer ligands 3 (a = 2,6-bis(ethanolimidazoliummethyl)pyridine diiodide, b = 2,6-bis(propanolimidazoliummethylpyridine)pyridine dibromide). The X-ray crystal structure of 4a is a one-dimensional linear polymer, whereas the mass spectroscopy confirms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
208
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 334 publications
(214 citation statements)
references
References 20 publications
3
208
0
3
Order By: Relevance
“…Further improvement of the bacteriostatic and antifungal activity has been achieved by encapsulating silver NHC complexes into polymers by electrospinning. 5 The modified polymer mats show bactericidal activities that are higher than the currently commercialized 1% silver sulfadiazine ointment…”
Section: Antimicrobial Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further improvement of the bacteriostatic and antifungal activity has been achieved by encapsulating silver NHC complexes into polymers by electrospinning. 5 The modified polymer mats show bactericidal activities that are higher than the currently commercialized 1% silver sulfadiazine ointment…”
Section: Antimicrobial Agentsmentioning
confidence: 99%
“…2). 5 Additionally, the 55 complex solutions with lower minimum inhibitory concentration (MIC) values inhibit the growth of microorganisms for a longer period than AgNO 3 . The higher activity may be rationalized by the partially covalent character of the Ag-C NHC bond, which provides enhanced stability and 60 decelerates silver dissociation.…”
Section: Antimicrobial Agentsmentioning
confidence: 99%
“…Caballero et al 17 reported a silver complex of bisimidazol-2-ylidene with a pyridine bridge; however, this complex is not polymeric. While the silver complexes described by Chen et al 44 and Melaiye et al 45 are oligomeric clusters, these complexes do not involve conjugation. Accordingly, the synthesis of stable metal complexes of polycarbenes remains a synthetic challenge.…”
Section: Heteroaromatic Biscarbenes Of the 124-triazole Seriesmentioning
confidence: 87%
“…In order to overcome these limitations, a variety of different metal containing complexes are currently being studied as potential anticancer agents. Among such compounds, the metal N-heterocyclic carbene (NHC) complexes are beginning to attract significant attention on account of their efficient drug design (Liu and Gust, 2013a) Of the various metal NHC complexes that have been prepared thus far, the silver and gold NHC complexes show considerable promise as anti-microbial and anticancer agents (Melaiye et al, 2004;Hickey et al, 2008b;Ozdemir et al, 2010;Elzatahry et al, 2012).…”
Section: Discussionmentioning
confidence: 99%